VD_FINDINFO Décision / 2011 / 691 vom 5. August 2011 - VD Tribunal cantonal (2011)
PROCÉDURE DE CONCILIATION, CITATION À COMPARAÎTRE, NON-LIEU, ASSISTANCE JUDICIAIRE | 135 al. 2 CPP (CH), 135 CPP (CH), 316 al. 1 CPP (CH), 319 al. 1 CPP (CH), 319 CPP (CH)